2021
DOI: 10.3390/nu13124221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti-Inflammatory Diets on Pain in Rheumatoid Arthritis: A Systematic Review and Meta-Analysis

Abstract: Various nutritional therapies have been proposed in rheumatoid arthritis, particularly diets rich in ω-3 fatty acids, which may lead to eicosanoid reduction. Our aim was to investigate the effect of potentially anti-inflammatory diets (Mediterranean, vegetarian, vegan, ketogenic) on pain. The primary outcome was pain on a 10 cm visual analogue scale. Secondary outcomes were C-reactive protein levels, erythrocyte sedimentation rate, health assessment questionnaire, disease activity score 28, tender/swollen join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 48 publications
1
42
0
3
Order By: Relevance
“…19 Fiber was increased above the recommended standard for adults because of its anti-inflammatory properties. 26,27 All products type included and not included in the LCHF and MFMC diets are shown in Table 1.…”
Section: Dietary Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Fiber was increased above the recommended standard for adults because of its anti-inflammatory properties. 26,27 All products type included and not included in the LCHF and MFMC diets are shown in Table 1.…”
Section: Dietary Interventionmentioning
confidence: 99%
“…Both diets maintained a ratio of n-6 to n-3 fatty acids of less than 4-5:1, which was to help reduce inflammation. 27 The study was aimed to compare effectiveness of two diets with caloric restrictions and different fat and carbohydrate contents in body weight and anthropometric parameter reduction in patients with lipedema. Body weight, waist and hip circumference, body fat, lower extremity body fat content as well as thigh and calf circumference measurements were used to evaluate effectiveness of the diets.…”
mentioning
confidence: 99%
“…A recent meta-analysis of seven randomized controlled trials (326 participants in total) was published to examine the effect of potentially anti-inflammatory diets (including, among others, vegetarian and Mediterranean) on pain in rheumatoid arthritis [Schönenberger et al, 2021]. Visual analogue scale (VAS), CRP level, erythrocyte sedimentation rate, health assessment questionnaire, disease activity score-28 for rheumatoid arthritis (DAS28), number of tender/swollen joints, body weight, and BMI were used for the assessment.…”
Section: Pain In Rheumatoid Arthritismentioning
confidence: 99%
“…However, the former dietary interventions were only evaluated in two papers. Nevertheless, the authors of the meta-analysis conclude that antiinflammatory diets, including vegetarian and Mediterranean diets, decrease pain in rheumatoid arthritis compared to traditional diets [Schönenberger et al, 2021]. However, as indicated the risk of bias was high, while the evidence was very low, advocating further studies to understand the role of vegetarian and Mediterranean diets in rheumatoid arthritis and comparison of outcomes of their implementation.…”
Section: Pain In Rheumatoid Arthritismentioning
confidence: 99%
“…A systematic review including two clinical trials and two prospective studies demonstrated that a Mediterranean diet has beneficial effects in reducing pain and increasing physical function in people with RA [ 24 ]. More recently, a meta-analysis found that anti-inflammatory diets including a Mediterranean Diet resulted in notably lower pain compared to habitual diets in people with RA (−9.22 mm; 95% CI −14.15 to −4.29; p = 0.0002; 7 RCTs, 326 participants) [ 25 ]. Given these encouraging outcomes, additional studies are needed to explore whether a Mediterranean dietary pattern could improve physical function and quality of life in people with RA.…”
Section: Introductionmentioning
confidence: 99%